Confirmatory Factor Analysis (CFA) Keberdayaan Rumah Tangga Terhadap Program Nasional Pemberdayaan Masyarakat Mandiri Pedesaan (PNPM-MP) di Kecamatan Situjuah Limo Nagari - Fitria Rahmona; Yulhendri Yulhendri (Universitas Negeri Padang, 2022)
The low level of empowerment illustrates the weak power of the household to meeting the basic needs of life. Increasing household power in meeting their daily needs can be done through community empowerment programs by utilizing the participation of the community. The government launched the PNPM-MP program uses the concept of empowerment as its operational approach. There are two programs implemented they are training and savings-loans programs. The statistical analysis in this study is Covariance Based Structural Equation Modeling (CB- SEM) using Smart PLS application. The study aims to determine the effect of implementing PNPM-MP programs on household empowerment in Situjuah Limo Nagari. The results of this study indicate that (1) Education and training have positive significant effect on household empowerment in Situjuah Limo Nagari. (2) training activities held by PNPM-MP have been good but not been able yet to increase the community's income to the maximum. (3) women's savings and loans have a significant effect on household empowerment. (4) an increase in community income after receiving SPP loan assistance from the PNPM-MP program.